2017
DOI: 10.1128/genomea.00226-17
|View full text |Cite
|
Sign up to set email alerts
|

Draft Genome Sequences of Two Highly Erythromycin-Resistant Streptococcus gallolyticus subsp. gallolyticus Isolates Containing a Novel Tn 916 -Like Element, Tn 6331

Abstract: Recently, we reported the draft genome sequence of Streptococcus gallolyticus NTS31106099. It was found to contain a previously unknown putative Tn916-like conjugative transposon, Tn6263. Here, we report the draft genome sequences of two other clinical isolates, NTS31301958 and NTS31307655. Both of them contain another novel element, Tn6331, which is highly similar to Tn6263.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Two of these isolates, NTS31301958 and NTS31307655, displayed different Tn6263 right-end amplicons (Figure S4a) and the only indistinguishable PFGE profiles (Figure S4b). Subsequent WGS 12 revealed that they contain another novel element, named Tn6331, which is highly related to Tn6263 (Figure S4c). Collectively, these results suggest that: (i) Tn6263 and/or related transposons are highly prevalent among the tested genetically heterogeneous Sgg isolates; (ii) they are the major ermB-carrying elements in the studied collection and; (iii) an integration hot spot for these elements is present in the chromosome of Sgg.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two of these isolates, NTS31301958 and NTS31307655, displayed different Tn6263 right-end amplicons (Figure S4a) and the only indistinguishable PFGE profiles (Figure S4b). Subsequent WGS 12 revealed that they contain another novel element, named Tn6331, which is highly related to Tn6263 (Figure S4c). Collectively, these results suggest that: (i) Tn6263 and/or related transposons are highly prevalent among the tested genetically heterogeneous Sgg isolates; (ii) they are the major ermB-carrying elements in the studied collection and; (iii) an integration hot spot for these elements is present in the chromosome of Sgg.…”
Section: Resultsmentioning
confidence: 99%
“…WGS is explained elsewhere. 11,12 Comparative analysis software and visualization is described at the end of the first Supplementary data file.…”
Section: Wgs and Comparative Analysismentioning
confidence: 99%
“…The pangenome is increasing at a high rate entailing numerous unique genes for each new strain added (Hinse et al, 2011b ). Nearly all SBSEC genomes reveal horizontal gene transfer relating to general carbohydrate metabolism, capsular polysaccharides, antimicrobial resistance or tannase as the key discriminator of SGG (Rusniok et al, 2010 ; Hinse et al, 2011b ; Lin et al, 2011b ; Jans et al, 2013 ; Papadimitriou et al, 2014 ; Kambarev and Caté, 2015 ; Grimm et al, 2017a ; Kambarev et al, 2017 ). Natural competence operons and pseudopilus identified in SII and SGG likely contribute to the success of horizontal gene transfer and thus to niche adaptation (Rusniok et al, 2010 ; Lin et al, 2011b ; Morrison et al, 2013 ; Jans et al, 2016 ).…”
Section: Transmission and Niche Adaption Of Sbsec Membersmentioning
confidence: 99%
“…One study on infant infection reported that the SGG strain was susceptible to penicillin, ceftriaxone, gentamicin and vancomycin [17]. Single SGG strains resistant to erythromycin have emerged [45].…”
Section: Streptococcus Gallolyticus Subsp Gallolyticus (Sgg)mentioning
confidence: 99%